Pott's Spine with Bilateral Psoas Abscesses - Sanjeevani Masavkar; Preeti Shanbag; Prithi Inamdar (Case Reports in Orthopedics)
A high degree of suspicion and appropriate imaging studies are required for the early diagnosis of Pott’s spine. We describe a 4-year-old boy with Pott’s disease of the lumbar spine with bilateral psoas abscesses. The child responded to conservative treatment with antituberculous treatment and ultrasonographically guided percutaneous drainage of the abscesses.